Chart Reader: Accessible Visualization Experiences Designed with Screen Reader Users - Thompson, John; Martinez, Jesse; Sarikaya, Alper; Cutrell, Ed; Lee, Bongshin (CHI '23: Proceedings of the ACM Conference on Human Factors in Computing Systems, 2023)
Even though screen readers are a core accessibility tool for blind and low vision individuals (BLVIs), most visualizations are incompatible with screen readers. To improve accessible visualization experiences, we partnered with 10 BLV screen reader users (SRUs) in an iterative co-design study to design and develop accessible visualization experiences that afford SRUs the autonomy to interactively read and understand visualizations and their underlying data. During the five-month study, we explored accessible visualization prototypes with our design partners for three one-hour sessions. Our results provide feedback on the synthesized design concepts we explored, why (or why not) they aid comprehension and exploration for SRUs, and how differing design concepts can fit into cohesive accessible visualization experiences. We contribute both Chart Reader, a web-based accessibility engine resulting from our design iterations, and our distilled study findings – organized by design dimensions – in the creation of comprehensive accessible visualization experiences.